2009
DOI: 10.1039/b818299j
|View full text |Cite
|
Sign up to set email alerts
|

Development of immunoassays to determinate sulfamethoxazole residues in wastewaters

Abstract: Different immunoassays have been developed to monitor sulfamethoxazole (SMX), an antibiotic frequently detected in water. The immunoassays were developed and optimized in two different formats: ELISA in polystyrene 96-well plate and microarray on compact disc (CD) support. Competitive microimmunoassays were performed by direct adsorption of immunoreagents on the polycarbonate surface of a low-reflectivity CD. Results were displayed using nanogold-labeled immunoglobulins and silver staining developer. High sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…3,4 As an alternative, antibody-based immunoassays such as the enzyme-linked immunosorbent assay (ELISA) have proven to be rapid, sensitive and a cost effective analytical tool for routine monitoring. 5,6 Many immunoassay methods used for determination of pesticides have been approved and listed by the U.S. Environmental Protection Agency (EPA). 7 Until now, most immunoassays available for the determination of OPs have been specific for only one single analyte.…”
Section: Environmental Impactmentioning
confidence: 99%
“…3,4 As an alternative, antibody-based immunoassays such as the enzyme-linked immunosorbent assay (ELISA) have proven to be rapid, sensitive and a cost effective analytical tool for routine monitoring. 5,6 Many immunoassay methods used for determination of pesticides have been approved and listed by the U.S. Environmental Protection Agency (EPA). 7 Until now, most immunoassays available for the determination of OPs have been specific for only one single analyte.…”
Section: Environmental Impactmentioning
confidence: 99%
“…To address this issue, Pastor-Navarro et al [73] reported a microarray method for sulfamethoxazole analysis via a microarray on a CD support, resulting in an LOD of 0.09 ng/mL. On a polycarbonate surface of a low-reflectivity CD, competitive microimmunoassays were conducted by direct adsorption of immunoreagents, followed by nanogold-labeled immunoglobulins and silver staining developer.…”
Section: Microarray Based Analysis Of Major Chemical Contaminantsmentioning
confidence: 99%
“…Morais et al, 2008), a neurotoxic compound(Tamarit-López et al, 2008), as well as pesticides and antibiotics in water)(Pastor-Navarro et al, 2009.…”
mentioning
confidence: 99%